Landscape Services Of Home Garden For Rural Household: A Case Study Of Jenggolo Village Malang Regency - Euis Elih Nurlaelih; Luchman Hakim; Arief Rachmansyah; Antariksa Antariksa (Socio-Economics/Agribusiness Department, 2019)
The home garden is a micro-scale landscape where interactions between humans and their environment intensively. One form of interaction is in the form of benefits provided by the home garden in the form of ecosystem services. This study aims to explore the landscape services of the home garden in Jenggolo Village, which are one of the villages that is part of a rice barn in Malang Regency. Data were collected by observation and semi-structured interviews. The results of the study indicate that the home garden provides complete ecosystem services including provisioning services, regulation services, and culture services. Provisioning services for food and cultural services are important home garden services for the household of Jenggolo Village, the majority of whom work as farmers and still cling to Javanese traditional culture. Awareness of the community towards the ecosystem services is one of the bases in determining a strategy for managing sustainable landscapes appropriately